A Case Report of Intraoperatively Diagnosed Cholangiocarcinoma after Unsuccessful Conservative Treatment of ERCP Complicated with Hemorrhage - Bozinovska Beaka, Gordana; Prgova Veljanovska, Biljana; Zdravkovska, Milka; Burova, Blagica (Vilnius University Press, 2018)
Cholangiocarcinoma is a malignant tumor arising from the epithelium of the bile ducts. Most of these tumors are adenocarcinomas [1]. Intrahepatic cholangiocarcinoma accounts for 10% of all cholangiocarcinomas, hilar cholangiocarcinoma for 25%, and extrahepatic cholangiocarcinoma for 65% [2, 3]. Cholangiocarcinoma can develop in any part of the extrahepatic duct, occurring in 50–75% of reported cases in the upper third of the duct including the hepatic hilum, in 10–25% in the middle third, and in 10–20% in the lower third [4–6]. Approximately 95% of cases show extrahepatic obstruction at the time of diagnosis [7]. In a meta-analysis of 21 prospective trials, the rate of hemorrhage as a complication of ERCP was 1.3% (95% CI, 1.2%–1.5%) with 70% of the bleeding episodes classiﬁed as mild [8]. Hemorrhagic complications may be immediate or delayed, with recognition of occurring up to 2 weeks after the procedure. The risk of severe hemorrhage (ie, requiring >5 units of blood, surgery or angiography) is estimated to occur in fewer than1 per 1 000 sphincterotomies [9]. Despite new and advanced diagnostic methods, sometimes this type of tumor is finally diagnosed from pathological findings on excised tissue.
Keywords: cholangiocarcinoma; ERCP hemorrhage; billiary stenosis